'Intervening early': agendas and rationalisations for children's developmental health. (1st August 2020) - Cressman, Celine; Miller, Fiona A.; Guttmann, Astrid; Cairney, John; Hayeems, Robin
Abstract : Background: Despite broad scientific consensus about the importance of the early years in the lifelong health and wellbeing of children, there is debate about whether and how healthcare professionals can optimise early child development through monitoring or screening. The evidence in support of a systematic population-level intervention is disputed, which is reflected in the diversity of approaches to developmental screening internationally. Methods: Using a case-study design, and interpretive qualitative methods, we explored how Canadian experts in child health (n=39): a) rationalise why they do, or would, pursue population-level developmental screening; b) articulate the policy goals of such an intervention, and; c) justify the practice with reference to evidence. Findings: Respondents identified three distinct framings, or policy agendas, for what developmental screening can and should seek to achieve, specifically: 1) as medical intervention, facilitating the early identification of health risk or disorder; 2) as social intervention, providing an opportunity for communication and connection with parents for all children; and 3) as political intervention, staking a claim for early child health on the broader political agenda. Discussion and conclusions: Each agenda is justified by distinct types of evidence, posing a challenge to simplistic models of evidence-based policymaking, and demonstrating that evidence is not just an input, but a contested part of a dynamic and political policymaking process.